“Can anything good come from Nazareth?” (John 1.46): Archeology and history of the birthplace of Jesus - Riesner, Rainer (Vox Scripturae - Revista Teológica Internacional, 2025)
According to archeological findings, Nazareth was founded in the 1st century BC. A Davidic clan chose the name in accord with the “sprout” (nezär) of Isaiah 11:1, expressing its messianic hope. Jesus lived for about thirty years in a devout Jewish place where the scriptures were read in the synagogue and Hebrew traditions were treasured.